Syntheses, Characterization, Resolution, and Biological Studies of Coordination Compounds of Aspartic Acid and Glycine - Temitayo Aiyelabola; Ezekiel Akinkunmi; Isaac Ojo; Efere Obuotor; Clement Adebajo; David Isabirye (Bioinorganic Chemistry and Applications)
Enantiomerically enriched coordination compounds of aspartic acid and racemic mixtures of coordination compounds of glycine metal-ligand ratio 1 : 3 were synthesized and characterized using infrared and UV-Vis spectrophotometric techniques and magnetic susceptibility measurements. Five of the complexes were resolved using (+)-cis-dichlorobis(ethylenediamine)cobalt(III) chloride, (+)-bis(glycinato)(1,10-phenanthroline)cobalt(III) chloride, and (+)-tris(1,10-phenanthroline)nickel(II) chloride as resolving agents. The antimicrobial and cytotoxic activities of these complexes were then determined. The results obtained indicated that aspartic acid and glycine coordinated in a bidentate fashion. The enantiomeric purity of the compounds was in the range of 22.10–32.10%, with (+)-cis-dichlorobis(ethylenediamine)cobalt(III) complex as the more efficient resolving agent. The resolved complexes exhibited better activity in some cases compared to the parent complexes for both biological activities. It was therefore inferred that although the increase in the lipophilicity of the complexes may assist in the permeability of the complexes through the cell membrane of the pathogens, the enantiomeric purity of the complexes is also of importance in their activity as antimicrobial and cytotoxic agents.